2014
DOI: 10.3171/2014.5.jns131736
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic absence of the posterior communicating arteries and the prediction of cognitive dysfunction after carotid endarterectomy

Abstract: Object Approximately 25% of patients exhibit cognitive dysfunction 24 hours after carotid endarterectomy (CEA). One of the purported mechanisms of early cognitive dysfunction (eCD) is hypoperfusion due to inadequate collateral circulation during cross-clamping of the carotid artery. The authors assessed whether poor collateral circulation within the circle of Willis, as determined by preoperative CT angiography (CTA) or MR angiography (MRA), could predict eCD. Methods Patients who underwent CEA after preopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 36 publications
2
7
1
Order By: Relevance
“…Type E posterior variant has been associated with increased risk of ischaemic stroke [8]. This variant is of importance to surgeons and neurologists in the evaluation of patients with intracranial tumors, traumatic injuries, and cardiovascular complications [29].…”
Section: Discussionmentioning
confidence: 99%
“…Type E posterior variant has been associated with increased risk of ischaemic stroke [8]. This variant is of importance to surgeons and neurologists in the evaluation of patients with intracranial tumors, traumatic injuries, and cardiovascular complications [29].…”
Section: Discussionmentioning
confidence: 99%
“…Whenever possible, we reviewed DSAs to determine PCOMs’ patency. TOF imaging is flow-dependent, and bidirectional flow through collaterals may lead to false signal loss and mischaracterisation of the vessel as being occluded 9. Conversely, contrast-enhanced CTA and MRA depict the vascular contour based on vessel patency.…”
Section: Methodsmentioning
confidence: 99%
“…Although cerebral hypoperfusion is common in patients with ICA stenosis, collateral circulation provides new paths to maintain sufficient blood supply even though it may only represent a poor compensation [2]. Some studies have investigated the association between collateral circulation and cognitive dysfunction in recent years; however, the findings on this topic have been inconsistent [3, 4]. Everts et al found no correlation between the formation of collaterals and cognitive function [5], while Sztriha et al proposed that collaterals-related perfusion restoration could improve the cognitive dysfunction [6].…”
Section: Introductionmentioning
confidence: 99%